Hidrolases e fenoloxidases de microrganismos como marcadores para seleção de biosuplementadores e avaliação do tratamento sobre efluentes sucroalcooleiros - Perovano Filho, Natalino (2007)
Due to the current and future problematic of the maintenance of the hydric resources, the reuse of waters after previous treatment has been a strategy in the management of aquifers. The bioaugmentation is one of the techniques of purification of effluents and, because of this, studies were carried out in lagoons from the station of treatment of effluents (STE) of one sugar-alcohol industry, in Coruripe, State of Alagoas, aiming its reuse in ferti-irrigation. Therefore, in the sugarcane harvests of 2004/05 and 2005/06, samples were collected respectively from residuary waters and turf of this STE, initially for isolation of microorganisms (agar-broth of sugar-cane 25%). The isolates were identified in agreement to its growth in differential media and microscopic morphology. The activities of extracellular enzymes were also evaluated. The isolates with characteristics of the genus Pseudomonas were cultivated in the media King A and B , agar-milk (production of caseinase) and in the system API 20E (Biomerieux), for identification at the level of species. The eight fungi isolated from the samples, as well as two fungi furnished by André Toselo Foundation (Phanerochaete chrysosporium and Geotrichum candidum), were evaluated in solid media according to their secretion of phenoloxidases, in special Lignin-Peroxidase and Tanase. All the ten fungi grew in these media, even so only some have generated halos of discoloration larger than the size of the colonies, as it happened with the isolate XXI identified as Cladosporium sp. This was able to degrade different azodyes, tannic acid and different natural phenolic substrates (sugar-cane bagasse and wood-dust) in solid and liquid media. When this fungus was cultivated in liquid medium with methylene blue, its growth curve and azodye discoloration, as well as its action on the variation of pH and electric conductivity, were evaluated. It was also compared its ability to remove total reducing glicids, proteins and phenols, as well as its production of Lignin-Peroxidase in liquid medium with methylene blue or natural phenolic substrates. Laccase was the probable phenoloxidase produced by the isolate of Cladosporium sp in these circumstances, mainly in natural substrates. It is possible that this fungus consumed the glicids released from the degradation of lignocellulosic polymers so that they didn t need to use the phenols during the time interval of the experiments (144 h). The best isolates to remove the azodye in the liquid medium containing 2 % of tannic acid, that is, Cladosporium sp and Aspergillus sp, were monitored according to the variation on the concentrations of total reducingglicids, proteins, phenols, and chemical oxygen demand (COD) in the media. The isolate of Cladosporium sp removed 12 % of the total COD of the media, against 9.3 % of removal by the isolate of Aspergillus sp, and both had reached the same rate of phenol reduction at the end of the evaluated period. Regarding to the samples of the agri-industrial effluent supplemented with only 1% of Carbon and Nitrogen composition of the Sabouraud-agar medium, it was observed that Mucor sp showed the best rates of reduction of COD and phenols, followed by the isolates of Cladosporium sp, P. chrysosporium and G. candidum. Finally, after the daily bioagumentation of the facultative lagoons from the studied STE (with an outflow of about 5.000 m3.h-1 and approximately 2 days of hydraulic retention), during the harvests of 2005/06 and 2006/07, by a consortium of 6 of the isolates tested in vitro, the monitoring of the physico-chemiscal parameters of biweekly collected water samples during both seasons showed that this strategy was promising, for having improved most of the quality parameters and turning the water appropriated for fertiirrigation. Even so, some of the characteristics did not obey yet the legislation got for launching in rivers (DO, COD and phosphates).